Explaining Continuance Intention of Fruit and Vegetable Consumption among the Rural Elderly: An Application of the Expectancy Confirmation Model - Mohamad Reza Jafari; Kambiz Ahmadi Angali; Hashem Mohamadian (The Scientific World Journal)
Background and Aim. Healthy aging is the permanent right of all people. Thus, the purpose of this work was to investigate the expectation confirmation model constructs on intention of continuing to consume fruit and vegetables among the rural elderly. Materials and Methods. This cross-sectional study was conducted on 332 elderly. The expectation confirmation model served as a theoretical framework. A random sampling was recruited. Data were collected through face-to-face visit in the second 6 months of 2016. The data were then analyzed using LISREL 8.5 and SPSS 16 software. Results. This model could explain 79% of intention to continue fruit and vegetable consumption. The usefulness and satisfaction had the most effect on the intention to continue the consumption of fruit and vegetables. Conclusion. Expectation confirmation model depicted a proper application in explaining the intention to continue the consumption of fruit and vegetables in the elderly. Since perceived benefits were the most important factor in determining the intention to continue F&V consumption in this study, it is required that policymakers utilize suitable efficient strategies to promote the perception of benefits of F&V consumption in the elderly by means of campaigns in the society, organizations, and families.